Advanced Composites with Natural Reinforcement - Jim, Low; Ian J., Davies; Yu, Dong; Uddin Ahmed, Shaikh Faiz; Hao, Wang; Md Akil, Hazizan (Hindawi Publishing Corporation, 2014)
The strict environmental regulations and depletion of petroleum resources urge the use of alternative eco-friendly natural reinforcements to produce advanced composites. These natural fillers or fibres such as sisal, coir, basalt, hemp, flax, and wool offer great renewability, biodegradability, abundance, cost effectiveness, and low specific gravity as opposed to synthetic fibres like glass and carbon. Composite industry realises enormous advantages of their composites in better functional or structural properties over synthetic counterparts despite not having relatively high mechanical performance.